Pendidikan Fikih Lingkungan dalam Membentuk Kesalehan Ekologis - Mufid, Muchamad; Novianti, Fitria (AN NUR: Jurnal Studi Islam, 2024)
The ecological crisis is entering a worrying phase with the excessive human exploitation of the environment. This article will discuss environmental education in shaping ecological integrity to cope with ecological crisis. This research is a qualitative study of library studies by collecting data from books, journals and related research sources. The results of the research include: first, the indicators of ecological integrity including, preserving, managing, improving and harnessing the environment in an optimal way. Second, environmental education has several purposes: building environmental awareness, enhancing environmental integrity, increasing environmental behaviour, increased active participation in ecological crises. Third, the environmental educational material among others reconstruction of the meaning of the caliph, ecological as the doctrine of Islamic teachings, and environmental destruction is ecological disbelief.